ANALISIS PEMASARAN JAMBU KRISTAL (Psidium guajava L.) DI DESA GADINGREJO KECAMATAN UMBULSARI KABUPATEN JEMBER - Rahmah, Jemima Almira; Hadi, Syamsul; Aulia, Anisa Nurina (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Crystal guava marketing is less efficient if the marketing channel is long. Long marketing channels will affect the amount of marketing costs and prices at the farmer and consumer levels. This study aims to: 1) how marketing channels are used, 2) calculate marketing margins, 3) determine marketing efficiency. The methods of this research are descriptive and quantitative. The location of the research was determined purposively, namely Gadingrejo Village, Umbulsari District, Jember Regency. The sampling technique uses total sampling and snowball sampling with a sample of 40 farmers and 10 marketing institutions. The results of this study show that: 1) There are 2 marketing channels of crystal guava, namely the channel pattern level II = Farmers → Wholesalers → Retailers → Consumers, the channel pattern level III = Farmers → Collectors → Wholesalers → Retailers → Consumers, 2) Each marketing channel pattern has a different marketing margin, namely the first marketing channel has a marketing margin of Rp 4,250/kg while the second marketing channel is Rp 4,250/kg 6,000/kg, 3) Efficient marketing channels are found in level II marketing channels with a farmer share value of 57.5% while in level III marketing channels with a farmer share value of 40%, the level II marketing channel pattern is more efficient compared to the level III marketing channel pattern.